2017
DOI: 10.1016/j.biomaterials.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted decellularization: an accelerated protocol to generate tissue-engineered human tracheal scaffolds

Abstract: Patients with large tracheal lesions unsuitable for conventional endoscopic or open operations may require a tracheal replacement but there is no present consensus of how this may be achieved. Tissue engineering using decellularized or synthetic tracheal scaffolds offers a new avenue for airway reconstruction. Decellularized human donor tracheal scaffolds have been applied in compassionate-use clinical cases but naturally derived extracellular matrix (ECM) scaffolds demand lengthy preparation times. Here, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 45 publications
3
66
0
Order By: Relevance
“…Scanning electron microscopy images shown in Figure a demonstrate that decellularization of muscle tissue in 0.25% SDS under 20 inHg (508 mmHg) of negative pressure during processing did not alter tissue morphology compared to matrices processed with the same detergent treatment under atmospheric pressure. This result is consistent with recently published work that showed intact tissue morphology in trachea decellularized under 1 Torr negative pressure, a stronger vacuum than used in our study (Butler et al, ). Athough we did not specifically test the effects of negative pressure on increasing efficiency of decellularization, a recent study using an SDS‐based method to decellularize trachea under 200 mmHg pressure compared to atmospheric pressure suggested they could reduce the treatment time from 72 to 48 hr while obtaining high decellularization efficiencies, which corroborates our anecdotal observation that negative pressure speeds decellularization (Xu et al, ).…”
Section: Resultssupporting
confidence: 94%
“…Scanning electron microscopy images shown in Figure a demonstrate that decellularization of muscle tissue in 0.25% SDS under 20 inHg (508 mmHg) of negative pressure during processing did not alter tissue morphology compared to matrices processed with the same detergent treatment under atmospheric pressure. This result is consistent with recently published work that showed intact tissue morphology in trachea decellularized under 1 Torr negative pressure, a stronger vacuum than used in our study (Butler et al, ). Athough we did not specifically test the effects of negative pressure on increasing efficiency of decellularization, a recent study using an SDS‐based method to decellularize trachea under 200 mmHg pressure compared to atmospheric pressure suggested they could reduce the treatment time from 72 to 48 hr while obtaining high decellularization efficiencies, which corroborates our anecdotal observation that negative pressure speeds decellularization (Xu et al, ).…”
Section: Resultssupporting
confidence: 94%
“…Recent studies applying vacuum-assisted decellularisation demonstrate increased decellularisation efficiency, especially with respect to complex organs that include dense tissues i.e. trachea and larynx [33,46]. The enhanced cellular clearance reduces the need for harsh physical or enzymatic treatments that may contribute to the loss of bioactive molecules from the ECM [33,46].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al () found that the microporous decellularized matrix fabricated by laser micropore technique (LMT) results in mild loss of ECM, which provides homogenous cell distribution of the matrix and good mechanical stability of graft under in situ condition. Butler et al () also reported that the vacuum‐assisted decellularization of tracheal graft results better graft for clinical application. Clinical study of acellular graft was done for the tracheal tissue reconstruction (Elliott et al, ; Etienne et al, ; Li et al, ; Martinod et al, ).…”
Section: Progress In Tracheal Tissue Engineeringmentioning
confidence: 97%